2020
DOI: 10.31219/osf.io/fxz3p
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Covid-19: acquired acute porphyria hypothesis

Abstract: Edited on account of feedback from Prof Read regarding the work of Liu & Li. Pandemic Covid-19 pneumonia, of SARS-CoV-2 aetiology, presents an existential threat to health care systems globally. Multiple therapeutic and prophylactic agents are currently undergoing clinical trial, including 23 clinical trials of (hydroxy)chloroquine in China. While progress towards a curative agent or vaccine is promising, the principal limiting factor in public health emergency is time, and therefore a pre-existing lic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the past, CD147 has been identified as a receptor for red blood cells for infection with the Plasmodium falciparum parasite (protozoan causing malaria in humans) [ 8 ]. Recent research shows that human red blood cells are strongly involved in the pathophysiology of COVID-19 [ 9 ].…”
Section: Dear Editormentioning
confidence: 99%
“…In the past, CD147 has been identified as a receptor for red blood cells for infection with the Plasmodium falciparum parasite (protozoan causing malaria in humans) [ 8 ]. Recent research shows that human red blood cells are strongly involved in the pathophysiology of COVID-19 [ 9 ].…”
Section: Dear Editormentioning
confidence: 99%
“…The current review advances the author's original hypothesis published as a preprint in April 2020 (Abrahams, 2020). Erythrocytes are strongly implicated in the pathophysiology of Covid-19 although their role is thought to be under-estimated.…”
Section: Introductionmentioning
confidence: 71%
“…However, when it is greater than 45%, there are signs of IO. When TS is >70%, a free form of iron begins to accumulate in the plasma, known as non-transferrin bound iron (NTBI) 4,6 , thereby causing IO in the parenchymal cells. Free Fe catalyzes the conversion of free radicals from oxygen.…”
Section: Iron Storagementioning
confidence: 99%
“…It has previously been demonstrated that SARS-CoV-2 binds to hemoglobin through ACE2, CD147, Cd26, and other receptors that are present on the surface of erythrocytes. After this association, virus attacks the beta1 chain of hemoglobin which leads to dysfunctional hemoglobin in addition to hemolysis, thereby reducing the oxygen supply to the body, causing tissue hypoxia, a remarkable characteristic of COVID-19 3,4 .…”
Section: Introductionmentioning
confidence: 99%